2003
DOI: 10.1002/mop.11329
|View full text |Cite
|
Sign up to set email alerts
|

Proposed OCDMA encoders and decoders based on silica‐on‐silicon integrated optics

Abstract: RESULTS Comparison with 2D ResultsTo test our code, we simulate the same problem as [8], used there to check focus properties of LHM. The problem consists of an infinitely long line source located 0 /2 above an LHM slab with thickness d ϭ 0 / 2, which is surrounded by free space. The LHM slab was located exactly in the middle of our domain, occupying x ϭ [0 120], y ϭ [40 80], and z ϭ [0 30] cells, including the PML region. The line source was located at (60, 100, [0 30]), 20 cells away from the slab and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2005
2005
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
3
0
4
Order By: Relevance
“…Na primeira, uma fonte de luz, como o diodo emissor de luz (LED) [79], apresenta seu espectro dividido através da utilização de filtros ópticos em um grande número de canais de comprimentos de onda, os quais são utilizados para efetuar as transmissões. Além dos tradicionais decodificadores utilizando linhas de atraso em fibra óptica [37], têm sido sugeridos outros artifícios como o emprego de cristais fotônicos [82] e óptica integrada [83]. Assim, cada bit é codificado em uma forma de onda s(t) que corresponde à sequência de assinatura do código [84].…”
Section: Técnicas De Acesso Múltiplounclassified
“…Na primeira, uma fonte de luz, como o diodo emissor de luz (LED) [79], apresenta seu espectro dividido através da utilização de filtros ópticos em um grande número de canais de comprimentos de onda, os quais são utilizados para efetuar as transmissões. Além dos tradicionais decodificadores utilizando linhas de atraso em fibra óptica [37], têm sido sugeridos outros artifícios como o emprego de cristais fotônicos [82] e óptica integrada [83]. Assim, cada bit é codificado em uma forma de onda s(t) que corresponde à sequência de assinatura do código [84].…”
Section: Técnicas De Acesso Múltiplounclassified
“…represented by an optical pulse of high amplitude and a short duration, where the duration of each chip is related to the code weight adopted by the specific code algorithm. Therefore, the full width at half maximum width (FWHM) of a chip is given by = / , where is the In addition to traditional ODLs [54], other artifices which use photonic crystals [55] and integrated optics [56] have been suggested. Each data information bit is encoded in a waveform that corresponds to a code signature.…”
Section: Time Encoding (1-d Encoding)mentioning
confidence: 99%
“…After substituting (57) and (58) into (56), it can be observed that the bipolar signal characteristics pushes the optimal threshold level to zero, i.e., , = 0. Then, after simple algebraic substitutions, and assuming that the interfering users are statistically independent, the average interference variance for interfering users can be expressed as the minimal BER for QPSK based networks as…”
Section: Qpsk Modulation Formatmentioning
confidence: 99%
“…When going through the process of coding, this bit period will be divided into L subintervals of duration T c denominated as chips. In addition to traditional ODLs [64], other techniques have been suggested such as the use of photonic crystals [65] and integrated optics [66].…”
Section: Coding In Time Domain Ds-ocdmamentioning
confidence: 99%